The boosting academic literacy for young learners’ reading comprehension and character building - Setiyo wahyuni, Elli; Wahyuni, Sri (JEES (Journal of English Educators Society), 2023)
Reading habit is important to be introduced to young learners. Through academic literacy, students not only comprehend social and science texts but also enhance their character. To realize the literacy program in these lessons, a team-game tournament is used that consists of a presentation, group discussion, reading tournament, and the award. The study uses a qualitative research method that applies a semi-structured observation guide and interviews sixth-grade students in one primary school in Indonesia. The observation indicates teaching techniques for improving reading comprehension, and the interview shows the impacts of academic literacy in the team-game tournament (TGT) on students’ knowledge. The findings show that academic literacy improves understanding of social and science texts, and moral values. This is an integrated skill because students get academic knowledge and character building. Students know how to comprehend passages related to social and science, as well as how to communicate the information through presentation skills. Academic literacy is proven to be an effective strategy to improve understanding and fluency in written and spoken forms. The study recommends that team-game tournament provides practices not only in reading but also in writing and speaking skills. Team-game tournament is an interesting learning method to have fun activity in the modern era of English teaching for young learners. HIGHLIGHTS: Academic literacy in team-game tournament (TGT) strategy is suggested to boost young learners’ reading comprehension and character building. Academic literacy improves the students’ understanding of social and science texts, and moral values. Academic literacy promotes fun learning in writing, reading, and speaking skills.